The metric dimension of the total graph of a semiring - Dolžan, David (Ukrains’kyi Matematychnyi Zhurnal, 2025)
UDC 512.5 We calculate the metric dimension of the total graph of a direct product of finite commutative antinegative semirings with their sets of zero-divisors closed under addition.